Organizing successful tournaments - Byl, John (Human Kinetics, 2014)
If you have been looking for a comprehensive collection of schedules and brackets that can be easily tailored to your events, then look no further. Organizing Successful Tournaments is the definitive resource that will put an end to your search! Whether you are running a three-team league, a huge tournament, or anything in between, the most competitive and fair schedule or bracket is at your fingertips in this package. This book shows you how to access more than 2,600 web-based Microsoft Word templates as the framework for virtually any tournament. These templates are programmed to automatically create draw sheets in minutes for competitions based on your input of divisions, seeds, locations, dates, and times. The book explains every major type of competition: Single elimination; Double elimination; Multilevel; Round-robin; Ladder; Pyramid; Level rotation. You'll also find information on assigning seeds, awarding byes, and establishing proper tiebreaking procedures. With Organizing Successful Tournaments, you will enjoy the organizing almost as much as the competition!